Myeloid Cells Enriched for a Dendritic Cell Population From People Living With HIV Have Altered Gene Expression Not Restored by Antiretroviral Therapy - Murray, Shannon M.; Zhang, Yuwei; Douek, Daniel C.; Sekaly, Rafick P. (Frontiers in Immunology, 2020)
Antiretroviral therapy (ART) for human immunodeficiency virus (HIV) infections has been designed to optimize CD4 T cell survival and limit HIV replication. Cell types other than CD4 T cells such as monocytes/macrophage, dendritic cells and granulocytes (collectively known as myeloid cells), are generally not considered in the development of ART protocols. Myeloid dendritic cells (mDC) are the most potent inducers of CD4 T cell activation and central to the regulation of immune responses. mDC in the blood are decreased in number, altered in function, and implicated in promoting HIV latency in People Living with HIV (PLWH). We found that cells enriched for mDC in PLWH had transcriptional changes compared to mDC from HIV uninfected individuals, some of which were not completely restored by ART. In contrast, other mDC functions such as interleukin-1 signaling and type I interferon pathways were restored by ART. Some of the transcriptional changes in mDC not completely reversed by ART were enriched in genes that are classically associated with cells of the monocyte/macrophage lineage, but new single cell RNA sequencing studies show they are also expressed by a subset of mDC. A cellular enzyme, acyloxyacyl hydrolase (AOAH), important for LPS detoxification, had increased transcription in mDC of PLWH, not restored by ART. It is possible that one reason ART is not completely successful in PLWH is the failure to phenotypically change mDC. Thus, inability of ART to be completely effective might involve myeloid cells and the failure to restore mDC function as measured by gene transcription. We suggest mDC and myeloid cells should be considered in future combination ART development.